Adrenergic Signaling in Circadian Control of Immunity - Leach, Sarah; Suzuki, Kazuhiro (Frontiers in Immunology, 2020)
Circadian rhythms govern a multitude of physiologic processes, both on a cell-intrinsic level and systemically, through the coordinated function of multi-organ biosystems. One such system—the adrenergic system—relies on the catecholamine neurotransmitters, adrenaline and noradrenaline, to carry out a range of biological functions. Production of these catecholamines is under dual regulation by both neural components of the sympathetic nervous system and hormonal mechanisms involving the hypothalamus-pituitary-adrenal axis. Importantly, both neural and hormonal arms receive input from the body’s central clock, giving rise to the observed rhythmic variations in catecholamine levels in blood and peripheral tissues. Oscillations in catecholamine signals have the potential to influence various cellular targets expressing adrenergic receptors, including cells of the immune system. This review will focus on ways in which the body’s central master clock regulates the adrenergic system to generate circadian rhythms in adrenaline and noradrenaline, and will summarize the existing literature linking circadian control of the adrenergic system to immunologic outcomes. A better understanding of the complex, multi-system pathways involved in the control of adrenergic signals may provide immunologists with new insight into mechanisms of immune regulation and precipitate the discovery of new therapeutics.